Acute Toxicity Test of Cocoa Seed Methanol Extract Mouthwash Against Mice - Cut Aja Nuraskin; Sisca Mardelita (Jurnal Online Keperawatan Indonesia, 2022)
Indonesia is famous for its natural wealth of medicinal plants. Cocoa plant (Theobroma cacao L.) is one of the herbal medicinal plants which is used as an alternative to cure diseases. Cocoa beans contain flavonoids, saponins and tannins which can inhibit the growth of bacteria and have potential as antioxidants and anti-bacterial. The calculation of the toxic test really needs to be taken into account in the experiment. Toxicity test is important to do to estimate the level of damage caused by a compound to biological and non-biological materials. Toxicity tests are generally used to determine unwanted effects of a drug, especially on the incidence of cancer, heart, liver and skin disorders or eye irritation. This study aims to determine the concentration of acute toxicity, safety level, cocoa bean mouthwash and the clinical symptoms it causes. The research method is a laboratory experiment based on the guidelines of the Organization for Economic Co-operation and Development (OECD). It uses minimal animal models, and testing time is relatively fast. A total of 12 female mice aged 6-8 weeks weighing about 25 g were divided into 4 treatments (n=4). Group 1 was given a dose of 1 mg/g BW, group 2 was given a dose of 2 mg/g, group 3 was given a dose of 3 mg/g and group 4 (control) was given 2 mL/kg BW of water. The extract was given orally using a sponge every day for 14 days. Research result; Based on the dose and death groups of mice after administration of methanol extract of Laban leaves, no dead mice were found either in the 1 mg/bb kg, 2 mg/bb kg dose group, the 3 mg/bb kg dose group, and the aquadest water control group. All 12 mice were alive. Based on the treatment dose group, the administration of methanol extract of Laban leaves after 24 hours and from the first day to the 14th day did not show symptoms of standing hair, incoordination of nerves, and did not show symptoms of depression, which meant that there were no symptoms of toxicity in mice. Based on body weight, each group showed an increase in body weight, the concentration given did not significantly affect body weight. Conclusion; Variation of the concentration of methanol extract mouthwash of cocoa beans was not toxic, did not cause death of rats, did not cause toxic symptoms and did not affect the body weight of rats. It is recommended to use methanol extract of cocoa beans as a basic ingredient for making mouthwash ingredients.